KEPEMIMPINAN TRANSFORMATIF DI LEMBAGA PENDIDIKAN - Syafnan Syafnan (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2010)
Leadership so central in attainment a purpose of institute nor organization. Leadership which trust and responsible can bring institute or organization of advance and grows. Leadership also very tightly of its(the bearing with power or power. Prospective leadership determined by the leader becoming top leader from an institute or organization. a leader must have leadership soul having the character of transformatif which sensitive of tehadap change and tunututan its(the area, so that organization led by it is permanent excise and becomes winner in competition of itself change. Leader of education must do orthogonal transformation of leadership through tuition giving, manual and fomentation to led by it that purpose of institute can be reached. Applying of leadership pattern of transformasional can support existence of change of institution-system.Kata kunci: transformatif of leaderships, institution, education